2020
DOI: 10.3892/ol.2020.11889
|View full text |Cite
|
Sign up to set email alerts
|

STAT1 expression and HPV16 viral load predict cervical lesion progression

Abstract: Cervical cancer is the fourth leading cause of cancer-associated mortality worldwide. However, its underlying molecular mechanisms are unclear. It is important to explore these mechanisms in order to identify novel diagnostic and prognostic biomarkers. The present study determined the association between STAT1 and human papillomavirus (HPV)16 in cervical lesions. STAT1 expression was detected by immunohistochemistry. Quantitative PCR was used to detect HPV16 viral load and STAT1 expression in cervical lesions.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 56 publications
1
13
1
Order By: Relevance
“…Our results regarding IHC-expression of STAT1 were in contrast to those of a recent study, which reported a higher STAT1-expression in cervical intraepithelial neoplasia (CIN) than in normal cervical epithelium, and deduced an association of increased STAT1-expression with malignant progression of CIN ( 26 ). Since STAT-1 expression is regulated by a complex network of interferons, we speculate that the difference in expression between vulvar and cervical tissue could be ascribed to the dissimilar microenvironments of these anatomical sites.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Our results regarding IHC-expression of STAT1 were in contrast to those of a recent study, which reported a higher STAT1-expression in cervical intraepithelial neoplasia (CIN) than in normal cervical epithelium, and deduced an association of increased STAT1-expression with malignant progression of CIN ( 26 ). Since STAT-1 expression is regulated by a complex network of interferons, we speculate that the difference in expression between vulvar and cervical tissue could be ascribed to the dissimilar microenvironments of these anatomical sites.…”
Section: Discussioncontrasting
confidence: 99%
“…For all tissue types, diffuse, cytoplasmic STAT1-expression of moderate-to-strong intensity was noted across full epithelial thickness. STAT1 is a component of the Janus kinase (JAK)-STAT signaling pathway, and can act as an antimicrobial mediator, a tumor suppressor, or a promotor of tumor progression ( 26 ). Aberrant expression of STAT1 in HPV-related lesions is considered to reflect activation of the JAK-STAT pathway as a consequence of the inflammatory response induced by HPV ( 26 ).…”
Section: Discussionmentioning
confidence: 99%
“…Given that ADC and SCC have frequently HPV 18 and 16, respectively, it is expected that this pathway is altered in both subtypes, nonetheless we were able to distinguish that it is enriched in the SCC subtype, which is an interesting fact that has yet to be validated. However, Wu S. and collaborators, reported that STAT1 expression, a member of this pathway, was positively correlated with HPV 16 viral load [33]. Therefore, if the SCC subtype has a higher HPV16 load, an increase activation of this pathway is expected.…”
Section: Discussionmentioning
confidence: 99%
“…It is well known that physical status of the virus (episomal or integrated forms) may generate variability in the host innate antiviral response ( 15 ). Therefore, a protein can be both downregulated by episomal papillomavirus and upregulated by integrated papillomavirus in infected cells being its expression positively associated with the progression of lesions ( 37 , 38 ). The lack of correlation between viral load and the expression of the studied antiviral immune response factors suggests that viral replication is not determinant in the E5-mediated downregulation of host immune responses.…”
Section: Discussionmentioning
confidence: 99%